The effect of open sun and indoor forced convection on heat transfer coefficients for the drying of papad - Kumar, Mahesh; Khatak, Pankaj; Sahdev, Ravinder Kumar; Prakash, Om (Journal of Energy in Southern Africa, 2011)
In this research paper, a simulation study has been carried out for the determination of convective heat transfer coefficients of papad under open sun drying and indoor forced convection drying modes. Experimental data obtained from open sun and indoor forced convection drying modes for papad were used to determine the values of the constants (C and n) in Nusselt number expression by using linear regression analysis, and consequently convective heat transfer coefficients were evaluated. The average values of convective heat transfer coefficients were found to be 3.54 and 1.56 W/m2 oC under open sun drying and indoor forced convection drying modes respectively. The experimental errors in terms of percent uncertainty were also evaluated.